2016
DOI: 10.1136/oemed-2016-103838
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of occupational hypersensitivity pneumonitis; reports from the SWORD scheme in the UK from 1996 to 2015

Abstract: ObjectiveTo estimate the reported incidence of occupational hypersensitivity pneumonitis (OHP) in the UK and to consider whether the pattern of attributed causation has changed over time.MethodsAll cases of OHP reported to the SWORD scheme between January 1996 and December 2015 were classified into 1 of 10 categories of the suspected agent. Cases were grouped into four 5-year time periods to examine any changing pattern in incidence or suspected causation. For each time period, the annual incidence was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 14 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…For occupational causes, the most commonly suspected exposures are to MWF or organic material (eg, compost, hay, leaves, soil, wood). This is entirely in keeping with data from the UK reporting scheme for occupational HP between 1996 and 2015, where exposure to MWF (35% of cases) and farming (17% of cases) were the most common causes 27. The reporting data demonstrated that over this time period, ‘Metalworking fluid HP’ has become the most commonly reported cause of occupational HP in the UK, a change in epidemiology that merits further research 28…”
Section: Discussionsupporting
confidence: 72%
“…For occupational causes, the most commonly suspected exposures are to MWF or organic material (eg, compost, hay, leaves, soil, wood). This is entirely in keeping with data from the UK reporting scheme for occupational HP between 1996 and 2015, where exposure to MWF (35% of cases) and farming (17% of cases) were the most common causes 27. The reporting data demonstrated that over this time period, ‘Metalworking fluid HP’ has become the most commonly reported cause of occupational HP in the UK, a change in epidemiology that merits further research 28…”
Section: Discussionsupporting
confidence: 72%
“…[1,2] Recently, the reported incidence of occupational HP in the United Kingdom was one to two cases per million workers per year. [3] The 1-year cumulative incidence rate ranged from 1.28 to 1.94 per 100,000 persons in the United States, which is lower than the incidence of idiopathic pulmonary fibrosis (IPF; approximately 6.8–16.3 per 100,000 persons). [4,5]…”
Section: Introductionmentioning
confidence: 99%
“…The causative organisms may vary from outbreak to outbreak, but we suggest that molecular-based screening of MWF and the monitoring of spatially clustered distributions of contamination could be useful in the early detection and prevention of what is now the most common cause of occupational HP in the UK. 28 …”
Section: Discussionmentioning
confidence: 99%